A RESPONSABILIDADE SOCIAL EMPRESARIAL COMO FERRAMENTA ESTRATÉGICA E MOTIVACIONAL NA INDÚSTRIA AUTOMOTIVA BRASILEIRA. ESTUDO COMPARATIVO DE CASO: VOLKSWAGEN DO BRASIL (GRANDE ABC) X FIAT AUTOMÓVEIS (BETIM/MG) - Silva, Mônica Roberta Aparecida (2008)
This paper is about to show the Social Responsibility as a competitive advantage, as well, a vital strategic tool to the survival of the companies in a scenery of frequently and fast changes. Emphasizing that, from the globalization on, with the fusion of cultures, many companies came, suddenly, into an extremely competitive environment, where, the oldies practices had to be abandoned because the client became the king . What means that he can choose whatever he wants and he is the mean reason of a company. To stand-up the informations, the comparative case study, by a qualitative descriptive research, between Volkswagen Brasil a germany company, installed over 50 years in Brazil and was the absolutely leader until the XXI century beginning but lost it to Fiat Automóveis an italian company, installed over 30 years in Betim, a city in Minas Gerais and was able to change a negative perception of the customers, adopting many actions, one of them was the Social Responsibility as a strategic and motivational tool to its internal public, in a clear social culture . Meanwhile, recently, Volkswagen suffered a tiring syndicate negotiation caused by the thousand employees demission in São Bernardo do Campo s unit, what made its´ acts and social precaution be demanded. The IPEA´s research of Social Indicators, second edition, is the guideline of this study that discloses: The Social Responsibility is still in the beginning in Brazil, the ISO26001 is in process, the environment preoccupation is being diffused all over the world and the managers, previously, worried exclusively about the profit, now are demanded for its choice and the possible social and environment impact.(AU)